Compulsory Interventions Are Challenging the Identity of Psychiatry - Hoff, Paul (Frontiers in Psychiatry, 2019)
Compulsory interventions severely restrict constitutional rights of the patients. They are exceptional measures only to be considered under strict and clearly defined ethical and juridical conditions. They do confront mental health professionals with difficult questions challenging their individual professional identity as well as the identity of psychiatry in general. This complex field is discussed in reference to the conceptual history of psychiatry, to different contemporary approaches to the notion of autonomy and to three ethically demanding issues: autonomy and care, psychiatry and society, personhood and interpersonal relations. Engaging open-mindedly in these debates may be cumbersome for psychiatry, but will yield a substantial return, particularly regarding its identity and acceptance by society.